Ocular tuberculosis II: Diagnosis and treatment [Oküer tüberküoz II: Tanı ve tedavi] - (:unkn) unknown (Turkish Ophthalmology Society, 2011)
Recent studies on the clinical importance of tuberculin skin tests (TST), interferon-gamma release assays (IGRAs), chest computed tomography (CT) and polymerase chain reaction have provided a new approach to diagnosing ocular tuberculosis (TBC). However, both TST and IGRAs cannot distinguish between latent TBC infection and active disease. Another corroborative test in the diagnosis of intraocular TBC is the evaluation of the lungs by either chest radiography or CT. Direct evidence for the diagnosis can be obtained by examination of smears and staining for acid-fast organisms, cultures of intraocular tissue/fluid for Mycobacterium tuberculosis, and nucleic acid amplification analysis. In recent years, guidelines have been suggested for the diagnosis of intraocular TBC. The current treatment of intraocular TBC consists of use of four drugs (isoniazid, rifampicin, ethambutol and pyrazinamide) taken for a long period of time (total 9-15 months).
Keywords: Diagnosis; Ocular involvement; Treatment; Tuberculosis; Uveitis